Development of Household Management Mobile Application - Lee, Shuan Qian; Firkhan Ali Hamid Ali, (Applied Information Technology And Computer Science, 2025)
Household management involves the strategic coordination and organization of resources within a family setting to meet the household's objectives and day-to-day needs. The "HouseLink" household management mobile application targets the prevalent disorganization in family management methods. Presently, disjointed approaches like handwritten notes and digital calendars hinder coherence and collaboration within households. To address this, the project aimed to create a specialized Android-based mobile application utilizing Android Studio IDE and Java for backend development, facilitating streamlined household management. Modules encompass user management, tasks, meal planning, and record-keeping, fostering collaboration and accessibility among family members. The study's significance lies in its potential to centralize household management, enhance collaboration, and simplify daily routines. Through a user-friendly interface, "HouseLink" aspires to empower families in achieving more coordinated and harmonious daily living.